Comparing performance and complexity of TCHB and CHB multilevel inverters using NLC technique - Hossain, Md. Showkot; Said, Nurul Ain Mohd; Halim, Wahidah Abd; Hossain, Md. Hasnat (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper presents a modulation strategy applied to a 13-level three-phase transistor clamped H-bridge (TCHB) inverter, aimed at a renewable and electric vehicle drives application. A comparison is performed between the TCHB inverter and a traditional cascaded H-bridge (CHB) inverter, considering circuit complexity, switching losses, and total harmonic distortion (THD) attained from each multilevel inverter topologies. The TCHB inverter achieves a 13-level output with only 15 switches, whereas the conventional CHB inverter requires 24 switches. The modulation technique, employing a nearest level control, yields improved output quality for both the TCHB and CHB multilevel inverters. The results demonstrate that this strategy effectively minimizes the overall THD. Notably, previous modulation techniques mainly focused on carrier-based PWM or SVPWM, making this approach distinctive. The FFT analysis reveals a voltage THD of 5.49% for TCHB and 5.15% for CHB, indicating a marginal difference in THD content for each multilevel inverter. Despite the CHB inverter experiencing double the switching stress compared to TCHB, since less switches are required in the TCHB inverter, consequently, the system's total cost and complexity are reduced. The achieved results are verified through the use of simulations carried out in the MATLAB Simulink.